Asistensi dan Pelatihan Pembuatan Video Promosi Pada Sapo Rumbia Villa and Cottage - Sinaga, Mikha; Sembiring, Nita Sari; Ginting, Erwin; Sinaga, Salsa Carissa; Sianturi, Charles Jhony Mantho; Sianturi, Noprita Elisabeth (Publikasi Pengabdian Masyarakat, 2024)
Sapo Rumbia Villa and Cottage is one of the accommodations located under the Gundaling Berastagi hill. Currently Sapo Rumbia accommodation has more than 40 rooms consisting of various types. Sapo Rumbia also has 1 villa which is located next to the accommodation. To market its villas and accommodation rooms, Sapo Rumbia uses videos recorded via cellphone cameras and without proper editing. Around the Sapo Rumbia inn there are many plantations owned by residents which can add a beautiful impression to the inn. Apart from plantations owned by residents, around the Sapo Rumbia accommodation there are also many views of hills and mountains that can pamper the eyes of tourists who stay at this accommodation. Sapo Rumbia Villa and Cottage does not explore the beauty of the surrounding nature in the promotional videos that have been made. Transitions between scenes in promotional video content have also not been made as attractive as possible so that it can increase people's desire to watch the video until the end. This activity also has several benefits, namely helping the management in promoting their villas and accommodation, making it easier for the public to obtain information regarding Sapo Rumbia Villa and Cottage, and increasing Sapo Rumbia's income from the promotions that have been made.